Thyroid Hormone Changes in Early Pregnancy Along With the COVID-19 Pandemic - Lin, Ting-Ting; Zhang, Chen; Zhang, Han-Qiu; Wang, Yu; Chen, Lei; Dennis, Cindy-Lee; Huang, Hefeng; Wu, Yan-Ting (Frontiers in Endocrinology, 2020)
Purpose: COVID-19 (Coronavirus Disease 2019) was first reported in December 2019 and quickly swept across China and around the world. Levels of anxiety and depression were increased among pregnant women during this infectious pandemic. Thyroid function is altered during stressful experiences and any abnormality during early pregnancy may significantly affect fetal development and pregnancy outcomes. This study is to find whether the COVID-19 pandemic would induce thyroid hormone changes in early pregnant women. Methods: This study comprised of two groups of pregnant women in Shanghai in their first trimester – those pregnant women before the COVID-19 outbreak from January 20, 2019, to March 31, 2019 (Group 1) and those pregnant during the COVID-19 outbreak from January 20, 2020, to March 31, 2020 (Group 2). All women were included if they had early pregnancy thyrotropin (TSH), free triiodothyronine (FT3), free thyroxine (FT4), total triiodothyronine (TT3), and total thyroxine (TT4) concentrations, thyroid peroxidase (TPO) antibody or thyroglobulin antibody (TgAb) available and did not have a history of thyroid diseases or received thyroid treatment before or during pregnancy. We used propensity score matching to form a cohort in which patients have similar baseline characteristics. Results: Among 3338 eligible pregnant women, 727 women in Group 1 and 727 in Group 2 had similar propensity scores and were included in the analyses. Pregnant women in Group 2 had significantly higher FT3(5.7 vs. 5.2pmol/L, P<0.001) and lower FT4(12.8 vs. 13.2pmol/L, P<0.001) concentrations compared with those in Group 1. Pregnant women in Group 2 were more likely to develop isolated hypothyroxinemia (11.6% vs. 6.9%, OR, 1.75 [95%CI, 1.20-2.53], P=0.003) than Group 1 but had significantly lower risk of TgAb positivity (12.0% vs. 19.0%, OR, 0.58 [95%CI, 0.43-0.78], P<0.001). Conclusion: Pregnant women in their first trimester in Shanghai during the COVID-19 outbreak were at an increased risk to have higher FT3 concentrations, lower FT4 concentrations, and isolated hypothyroxinemia. The association between thyroid hormones, pregnancy outcomes, and the COVID-19 outbreak should be explored further.